(untitled) (Journal of the College of Basic Education, 2023)
Humans settled in two types of environments: the natural environment, which consists of water and air. Soil, plants, and animals, which preceded the emergence of man by millions of years, and from which we were created, and to which we shall return. As for the second type of environment, it is the artificial and social environment that we create for ourselves using Scientific and technical means, social and political systems, whether the environment is natural or artificial. It is an essential task for human life and health, and when a person deals with his environment and interacts with it, he